Role of Renewable Energy Sources in the World - Mammadov N.S.; Ganiyeva N.A.; Aliyeva G.A. (Journal of Renewable Energy, Electrical, and Computer Engineering, 2022)
The severe climate crisis on the planet has led to the need to quickly abandon fossil fuels and switch to alternative energy, "green" energy sources. This article discusses the main types of alternative energy. It is shown that new types of energy play an important role in the energy supply systems of most countries of the world, and in the future they can become the main sources of energy to meet the growing needs of the world economy. The main reasons for the growing interest in RES are revealed. Their advantages and disadvantages are considered, on the basis of which you can find out which one is the most profitable. The ways and purposes of using solar energy and wind energy are given. The advantages of renewable energy sources in comparison with traditional energy sources are considered.